Compartment Syndrome of the Hand: A Little Thought about Diagnosis - Reichman, Eric F. (Case Rep Emerg Med, 2016)
Compartment syndrome of the forearm is a well described entity but there have been relatively few case reports in the emergency medicine literature of hand compartment syndromes (HCS). Prompt recognition and treatment of this potential limb threat are essential to minimize morbidity and mortality. Presented is a case of a documented hand compartment syndrome following a motor vehicle collision.